Application of Permanent Magnet Generator for Electric Vehicle - LI Huaxiang; HU Yongfeng (Kongzhi Yu Xinxi Jishu)
It discussed variable speed and variable load operation modes of permanent magnet generator (PMG) and its output characteristics matching to the engine. Full-wave rectification is used in the output of PMG and engine unit to adjust the electric power output by controlling its operating speed. Generators and batteries are designed in parallel in the in-car power supply system. In order to satisfy power requirements of electric vehicle and reduce its fuel consumption, battery terminal voltage is used as reference and optimized strategy is applied to supply power for the motor drive system.